Global Civil Registration and Vital Statistics : A Scaling Up Investment Plan 2015-2024 - World Bank (World Bank Group, Washington, DC, 2014)
The UN Economic Commission for Africa (UNECA), WHO, and the World Bank co-hosted a global consultative meeting on Civil Registration And Vital Statistics (CRVS) in Addis Ababa on April 28-29, 2014 to discuss and obtain input on a draft investment plan. Civil registration is the act of recording and documenting of vital events in a person s life (including birth, marriage, divorce, adoption, and death) and is a fundamental function of governments. The goal of the Civil Registration and Vital Statistics (CRVS) plan is to register births, deaths and other vital events, including reporting cause of death, and access to legal proof of registration for all individuals by 2030. This global plan has three key components concerning the following: 1) national CRVS strengthening that removes the barriers to birth registration, improving reporting of deaths and determining cause of death, strengthening CRVS institutions and ICT systems, strengthening national ID mechanisms, and improving the response to deaths and vital statistics; 2) international support for CRVS that will focus on strengthening international standards for CRVS, and preparing and sharing guidance based on country experience; and 3) sharing knowledge and building the evidence base that analyzes barriers and programs of implementation research, together with rigorous impact evaluation, that will share lessons on what works in different situations.